Modelling of business processes by computerimitation - Kosynskyi, Valentyn (Publishing House of the Wrocław University of Economics, 2009)
In a crisis an ability to react flexibly on critical changes of the market environment is vital, because the crisis calls the prompt reaction. On the other hand decisions should remain effective. Efficiency in decision-making is provided with constant monitoring of dynamics for business processes, efficiency – with an estimation of decisions by means of computer modelling for possible variants. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 247-252